Romanian adolescents, fake news, and the third-person effect: a cross-sectional study. Issue 3 (3rd July 2022) - Corbu, Nicoleta; Oprea, Denisa-Adriana; Frunzaru, Valeriu
ABSTRACT: Despite their apparent digital literacy, adolescents often have trouble assessing the accuracy and trustworthiness of the information they encounter. Given the proliferation of fake news and that adolescents are new (or soon-to-be) voters, important issues arise for democratic processes. This study is the first to investigate Romanian adolescents' self-perceived ability to evaluate the credibility of the news in their media diet. Drawing on a national survey (N = 1, 221) of 12th-grade Romanian students (aged 17–18), we found a significant third-person effect in young people's self-reported ability to detect fake news. This effect is stronger when people compare themselves to distant others than close others. We also found that the most important predictors of this third-person effect are gender, openness to multiculturalism, and lifelong learning, with family education and confirmation bias being non-significant predictors. IMPACT SUMMARY: Prior State of Knowledge : Prior studies show that although adolescents are increasingly aware of the prevalence of fake news, they have difficulty assessing news accuracy. Less is known about how adolescents perceive their capabilities to assess accuracy as compared with their friends and family or with other people in general. Novel Contributions : Romanian adolescents exhibit a strong third-person effect, meaning that they consider themselves more capable of identifying false information than peers in their inner and outer circles. The prevalence of this perception raises serious concerns about their ability to be well-informed participants in the democratic process. Practical Implications : Romanian policymakers should introduce media literacy into high school curricula to develop students' abilities to assess news accuracy, fact check information, and be better prepared to enter adulthood as informed citizens.